Received signal strength indicator and network reliability performance analysis for landslide monitoring system based on IEEE 802.15.4 standard - Perdana, Doan; Sumaryono (International Journal of Innovative Research and Scientific Studies, 2025)
This research aims to evaluate the effectiveness of the Received Signal Strength Indicator (RSSI) and the reliability of the network in a landslide monitoring system that adheres to the IEEE 802.15.4 standard, while emphasizing the impact of several key environmental factors and the scalability of the system on network performance under actual field conditions. The research approach is carried out experimentally through the implementation of a wireless sensor network architecture using ZigBee end devices integrated with rotary encoder sensors, vibration sensors, soil moisture sensors, and accelerometer-gyrometer sensors. System performance evaluation is conducted by considering variations in environmental conditions, including slope angle and slope, soil composition, rainfall intensity, signal attenuation due to terrain contours, landslide-prone zones, and seismic activity. Furthermore, the impact of increasing the quantity of sensor nodes on the reliability of the network is also examined thoroughly. The results showed that the RSSI value tended to decrease (becoming increasingly negative) along with increasing distance, increasing slope angle, and an increasing number of sensor nodes. The signal strength range was recorded between -62 dBm to -120 dBm based on variations in slope angle and terrain contour characteristics, with more significant signal degradation on steeper slopes. Meanwhile, under conditions of varying rainfall intensity, the RSSI value also experienced a significant decrease due to increasing distance, rainfall intensity, and the number of installed sensors, with a signal strength range between -65 dBm to -110 dBm. This research indicates that the characteristics of the terrain and weather conditions, particularly the angle of the slope and the intensity of rainfall, significantly affect the integrity of signals and the performance of networks in landslide monitoring systems.